Icariin promotes the repair of PC12 cells by inhibiting endoplasmic reticulum stress - Chengjie Wu; Guanglu Yang; Yalan Pan; Lei Wang; Pengcheng Tu; Suyang Zheng; Yang Guo; Yong Ma (BMC, 2021)
Abstract Background Endoplasmic reticulum stress (ERS) is one of the main mechanisms of spinal cord injury (SCI) pathology and can affect the physiological state of neurons. Icariin (ICA), the main pharmacological component of Epimedium, can relieve the symptoms of patients with SCI and has obvious protective effects on neurons through ERS. Methods PC12 cells were induced to differentiate into neurons by nerve growth factor and identified by flow cytometry. Cell proliferation was detected by CCK8 method, cell viability was detected by SRB assay, apoptosis was detected by flow cytometry and microstructure of ER was observed by transmission electron microscope. Western blot was used to detect the protein expression of CHOP and Grp78, and qPCR was used to detect the mRNA expression of CHOP and Grp78. Results The results of CCK8, SRB and flow cytometry showed that ICA could relieve ERS and reduce apoptosis of PC12 cells. The results of transmission microscope showed that ICA could reduce apoptosis of PC12 cells caused by ERS. The results of Western blot and q-PCR showed that ICA could inhibit ERS by down-regulating the expression of CHOP and Grp78. Conclusions ICA can inhibit ERS and promote the repair of PC12 cells by down-regulating the expression of CHOP and Grp78. ICA has the potential to promote the recovery of spinal cord injury.